2014
DOI: 10.2147/imcrj.s76214
|View full text |Cite
|
Sign up to set email alerts
|

Wound management with vacuum-assisted closure in postoperative infections after surgery for spinal stenosis

Abstract: ObjectiveTo evaluate the results of negative-pressure wound therapy (NPWT) in the treatment of surgical spinal site infections.Materials and methodsThe use of NPWT in postoperative infections after dorsal spinal surgery (transforaminal lumbar interbody fusion plus posterior instrumentation) was studied retrospectively. From February 2011 to January 2012, six patients (females) out of 317 (209 females; 108 males) were readmitted to our clinic with surgical site infections on postoperative day 14 (range 9–19) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 16 publications
0
26
0
5
Order By: Relevance
“…The literature is emerging when it comes to negative-pressure therapy, especially in orthopaedic or plastic surgery. Different authors reported a positive effect of negative-pressure vacuum therapy of spinal SSI, but again none of the studies are comparative (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is emerging when it comes to negative-pressure therapy, especially in orthopaedic or plastic surgery. Different authors reported a positive effect of negative-pressure vacuum therapy of spinal SSI, but again none of the studies are comparative (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Any benefits of long-term antibiotic use remain to be determined (3). Other recent options and recommendations include hyperbaric oxygen, negative-pressure vacuum wound therapy (13)(14)(15), closed suction irrigation systems (2,16), or local antibiotic use (17). However, comparative data supporting these individual recommendations are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, continuous negative pressure at a relatively high level of -200 to 300 mmHg was used on the wound beds. This suction protocol was used as it had previously been observed to be effective in clinical practice and as stronger suction was not considered since intense negative pressure may increase the risk of hemorrhage (10). Intermittent suction was additionally avoided due to potential patient intolerability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the merits of NPWT compared with traditional methods in the treatment of complex wound defects (8). Despite a lack of high-level evidence, studies have indicated that NPWT may facilitate wound healing, prepare the wound bed for skin grafts or flaps, decrease the risk of infection and reduce the labor of clinicians (9)(10)(11). Conventional indications for NPWT include traumatic wounds, wounds with acute or chronic infections, ulcers, diabetic foot ulcers, dehiscent wounds and burns (12).…”
Section: Introductionmentioning
confidence: 99%
“…После формирования отрицатель-ного давления края раны сближают, а содержи-мое раны эвакуируют наружу. На сегодняшний день существуют лишь единичные сообщения об использовании вакуум-ассистированного за-крытия ран в спинальной нейрохирургии, что не позволяет высказаться о доказанной эффектив-ности этого метода [48][49][50].…”
Section: таблицаunclassified